2022
DOI: 10.3390/coatings12040427
|View full text |Cite
|
Sign up to set email alerts
|

Impact Abrasive Wear Resistance of CrN and CrAlN Coatings

Abstract: The impact wear resistance of the hard coating is very important in the high-temperature environment of the nuclear power plant. CrN and CrAlN coatings were prepared using multi-arc ion plating. The impact abrasive wear resistance of the coatings was investigated at varied temperatures through a controlled kinetic energy impact wear rig, and their impact mechanism was elucidated. No extensive spalling was found on the surface of the CrN and CrAlN coatings after 104 impacts under the no-sand condition. The exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Based on the literature, it is clearly demonstrated that different contact and/or failure mechanisms occur at the coating/counterbody contact interfaces, as illustrated in the flow diagram in Figure 1. The major wear mechanisms of coatings at elevated temperatures include wear particle adhesion on the interacting surface, abrasive wear, excessive oxidation, phase transformations, chipping, cutting, mechanical property weakening, and coating delamination from substrates [21][22][23].…”
Section: Coating Contact/failure Mechanisms At Elevated Temperaturesmentioning
confidence: 99%
“…Based on the literature, it is clearly demonstrated that different contact and/or failure mechanisms occur at the coating/counterbody contact interfaces, as illustrated in the flow diagram in Figure 1. The major wear mechanisms of coatings at elevated temperatures include wear particle adhesion on the interacting surface, abrasive wear, excessive oxidation, phase transformations, chipping, cutting, mechanical property weakening, and coating delamination from substrates [21][22][23].…”
Section: Coating Contact/failure Mechanisms At Elevated Temperaturesmentioning
confidence: 99%
“…Knowing the change in velocity, the kinetic energy response in the impact process can be deduced using the kinetic energy theorem E = the impact block and the tube sample is mainly used for plastic deformation, friction and wear, crack initiation and propagation, oxidation, etc. [33]. Table 2 shows the experimental parameters of the impact wear test.…”
Section: Experimental Equipment Parametersmentioning
confidence: 99%
“…In the works [27,28], the principles of operation of the technique for carrying out nano-, micro-and macroscale impact tests of coatings are considered. The peculiarities of the determination of wear resistance in the conditions of field tests for abrasion and shock-abrasive wear and the measurement of hardness using indentation are considered in the publications [29,30]. The detailed review [31] presents a portfolio of methods for determining the microstructural, mechanical and thermophysical characteristics of solid coatings, which allow an understanding of the relationships between the structure and properties of the coating.…”
Section: Introductionmentioning
confidence: 99%